Programmatic Challenges in Implementing PMTCT Option B+ and Pediatric HIV Care: Baseline Assessment from “Save the Families for Africa” in Malawi - Fokam, Joseph; Santoro, Maria Mercedes; Chimbiri, Isabel; Chindiura, Jeremoni; Deula, Ruth; Rombe, Alex; Massari, Riccardo; Lungu, Agness; Perno, Carlo-Federico (HEALTH SCIENCES AND DISEASE, 2019)
ABSTRACT Objective. With high rates of HIV-infection among pregnant women living in sub-Saharan Africa (SSA), risks of mother-to-child transmission (MTCT) remain concerning in spite of current progress. Thus, identifying gaps in the era of option-B+ would generate specific evidence-based interventions. Methods. A baseline assessment for “SAVE THE FAMILIES FOR AFRICA” project, a retrospective study was conducted throughout 2014 at the Likuni Mission Hospital in Malawi based on performance indicators of the prevention of MTCT (PMTCT) cascade and pediatric antiretroviral therapy (ART) care. Results. In 2014, 7.5% (199/2658) newborns were vertically exposed to HIV and all HIV-infected mothers (199) received PMTCT intervention. A rate of 40.8% and 55.1% HIV-infected pregnant/breastfeeding mothers were lost to follow-up at six and 12 months, respectively. Amongst infants (6 [IQR: 6-8] weeks) tested for HIV-1 early infant diagnosis (EID), 79.0% (166/210) EID results were withdrawn, with a median turn-around time (TAT) of 36 [IQR: 30-60] days. 82.5% mothers were on lifelong ART 4 weeks before delivery. Infants received cotrimoxazole (100.0%), nevirapine prophylaxis (91.2%) and exclusive breastfeeding (90.8%). HIV-1 MTCT was 2.8% (6/215), with higher age (p=0.07) and longer TAT (p=0.367) among infected-infants. For pediatric ART, dispensing practices and drug supply were excellent (100%), while on-time drug pick-up (69.7%) and retention in care (70.9%) were poor. Conclusions. Progress in option-B+ and pediatric ART care are encouraging in this SSA setting, but may be hampered by lost to follow-up and poor adherence. Eliminating MTCT and sustaining pediatric ART performance in SSA require a holistic interventional approach for universal access to healthcare. RÉSUMÉ Objectif. La forte prévalence du VIH chez les femmes enceintes en Afrique sub-Saharienne (SSA) suggère un risque considérable de la transmission mère-enfant (TME) malgré progrès enregistrés. Dans cette optique, identifier les goulots d’étranglement dans l’ère option-B+ permettrait la mise en œuvre des interventions probantes. Méthodes. Une étude retrospective a été menée dans le cadre du projet “SAVE THE FAMILIES FOR AFRICA” durant l’année 2014 à l’Hôpital Missionnaire de Likuni au Malawi, sur la base de la performance des indicateurs de la cascade en prévention de la TME (PTME) et prise en charge du VIH pédiatrique (ART). Résultats. Durant cette année, 7,5% (199/2658) de nouveaux nés avaient subi une exposition verticale au HIV et toutes les femmes enceintes infectées par le VIH (199) étaient enrôlées dans la PTME MTCT. Un taux de 40,8% et 55,1% des femmes enceintes/allaitantes était perdue de vue à six et à 12 mois après enrôlement. Parmi les enfants (6 [IQR: 6-8] d’âge semaines) testés pour le diagnostic précoce du VIH (EID), 79,0% (166/210) des résultats étaient retirés, dans une délai de 36 [IQR: 30-60] jours. 82.5% des mères étaient sous trithérapie antirétrovirale (TARV) 4 au moins 4 semaines avant l’accouchement. La prophylaxie au cotrimoxazole était de 100,0% chez les enfants, prophylaxie à la nevirapine de 91,2% et l’allaitement maternel and exclusif de 90,8%. le taux de TME était de 2,8% (6/215), légèrement élevé avec l’âge avancé (p=0,07) et le temps de retrait de résultats (p=0,367). Concernant la TARV pédiatrique, les practices de dispensation et la délivrance des médicaments étaient excellentes (100%), les taux de retrait des médicaments dans les délais (69,7%) et de rétention (70,9%) étaient faibles. Conclusions. L’option-B+ s’accompagne d’excellents progrès en PTME et prise en charge pédiatrique du VIH au Malawi. Une optimisation des performances nécessite des interventions visant à limiter les perdues de vue et les cas d’inobservance, a travers une approche holistique autour du couple mère-enfant.